Incorporation of Deoxyviolacein Functional Dye into PHB and Cellulose Double Layered-Biodegradable Polymer - Park, Seo A.; Ahn, Soo Yeon; Choi, Kwon Young (Journal of Polymers and the Environment, 2023)
In this study, deoxyviolacein-incorporated poly-β-hydroxybutyrate-cellulose biopolymer (PHB-DV-Cell) was simultaneously produced. The monomers of PHB, a well-known semi-crystalline biodegradable polymer, were synthesized simultaneously in a deoxyviolacein-producing host cell, whereas cellulose, a naturally occurring biopolymer, was extracellularly supplied. Simultaneously, L-tryptophan-derived deoxyviolacein was incorporated to enhance the mechanical and biological properties of PHB, followed by compositing cellulose with the deoxyviolacein-incorporated PHB polymer (PHB-DV). Cellulose was then supplied to PHB-DV for PHB-DV-Cell layered film production. Polymeric and biological functionalities such as thermostability, antioxidant capacity, biodegradability, and tyrosinase inhibitory activity of PHB-DV-Cell were analyzed. Interestingly, the incorporation of deoxyviolacein between PHB and cellulose resulted in higher resistance to biodegradation and lowered antioxidant capacity, whereas thermostability was not greatly affected, suggesting that the functional deoxyviolacein molecules were stably maintained between the two biodegradable films. Significant changes in biodegradability, analyzed through co-cultivation with PHB-degradable Ralstonia eutropha, were observed with PHB-DV-Cell, and could be tightly bound to the films. Finally, PHB-DV-Cell exhibited unusual surface features without discoloration. These findings could contribute towards the development of biodegradable polymers with applicable functionalities and controllable biodegradability.
Keywords: Antioxidant capacity; Cell-be; Cell/B.E; Cell/BE; Deoxyviolacein; Double layered; Functional dyes; PHB; Poly-β-hydroxybutyrate; Semicrystallines; Biopolymer; Cellulose film; Deoxyviolacein; Functional polymer; PHB